2014
DOI: 10.2147/odrr.s46018
|View full text |Cite
|
Sign up to set email alerts
|

Orphan drugs in glioblastoma multiforme: a review

Abstract: Glioblastoma multiforme (GBM) is the most common and deadly brain tumor in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 83 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…While some of the substances that we highlight here were already discussed and contained in a review by Lassen et al [ 18 ], the surge in immunotherapeutic approaches which we highlight here seems noteworthy. For many of these novel, immunotherapeutic products, no efficacy data in the sense of randomized, placebo-controlled trials have been published.…”
Section: Discussionmentioning
confidence: 92%
“…While some of the substances that we highlight here were already discussed and contained in a review by Lassen et al [ 18 ], the surge in immunotherapeutic approaches which we highlight here seems noteworthy. For many of these novel, immunotherapeutic products, no efficacy data in the sense of randomized, placebo-controlled trials have been published.…”
Section: Discussionmentioning
confidence: 92%
“…In 2017, the Wick et al RCT concluded that CCNU in combination with bevacizumab did not provide a survival advantage compared to CCNU alone (OS: 9.1 vs. 8.6 months; PFS: 4.2 vs. 1.5 months) [ 39 ]. CCNU is considered the key factor in the PCV regimen (P: procarbazine, C: lomustine, V: vincristine) which has been approved by the FDA as a regimen for HGGs [ 41 ]. In 2010, the Brada et al RCT compared PCV to TMZ in patients with recurrent HGGs; they concluded PCV did not differ significantly in OS (6.7 vs. 7.2 months), PFS (3.6 vs. 4.7 months), quality of life, or adverse events [ 42 ].…”
Section: Fda-approved Therapiesmentioning
confidence: 99%
“…1 Lessen et al stated that “the PCV regimen is frequently utilized as a control regimen in randomized phase III studies and has recently received FDA approval for recurrent HGG”. However, the given data only serve as level III evidence, 34 and no evidence could be found to classify it in the FDA-approved regime, and thus PCV is classified as a non-FDA-approved drug and discussed in the following section.…”
Section: Current Drugs For Gbm Treatmentmentioning
confidence: 99%